THE RELATIONSHIP BETWEEN GENDER AND THE LEVEL OF DEPRESSION AMONG STUDENTS IN INDONESIA: A CROSS-SECTIONAL STUDY - Sa’adah, Irma Hanifatu; Wardani, Rifka Pramudia; Wardani, Yuniar Laksmi Eka; Aini, Wahyu Nur; Sari, Jayanti Dian Eka (Lembaga Penelitian dan Terapan untuk Kesehatan Jiwa (Lenterakaji), 2024)
Background: College students are vulnerable to depression and anxiety, which are the main symptoms of mental emotional disorders that often occur today. Student depression can occur in female students or male students. The prevalence of mental illness characterized by symptoms and anxiety in the population aged 15 years and over is 6.1% of the total population. Purpose: The purpose of this study was to determine the relationship between gender and the incidence of depression in college students. Methods: This study used quantitative methods with data collection by incidental sampling on 54 (consisting of 36 women and 18 men) active students of the 6th semester of FIKKIA Universitas Airlangga Banyuwangi. Data collection was done online and analyzed using chi-square, using the CES-D instrument. Results: The results of the study found no relationship between gender and the level of depression in sixth semester students, with a value of ρ = 0.325 from the chi-square test, which shows there is no relationship between gender and depression. Conclusion: In this study it showed no relationship was found between gender and levels of depression in students. Abstrak Latar Belakang: Mahasiswa rentan terhadap depresi maupun kecemasan, yang merupakan gejala utama dari gangguan mental emosional yang sering terjadi saat ini. Depresi mahasiswa dapat terjadi pada mahasiswa perempuan ataupun mahasiswa laki-laki. Prevalensi penyakit jiwa yang ditandai dengan gejala dan kecemasannya pada penduduk usia 15 tahun ke atas yaitu 6,1% dari total penduduk. Tujuan: Tujuan penelitian ini untuk mengetahui hubungan antara jenis kelamin dengan kejadian depresi pada mahasiwa. Metode: Penelitian ini menggunakan metode kuantitatif dengan pengambilan data dengan incidental sampling pada 54 (terdiri dari 36 orang perempuan dan 18 orang laki-laki) mahasiswa aktif semester VI FIKKIA Universitas Airlangga Banyuwangi. Pengumpulan data dilakukan secara daring dan dianalisis menggunakan chi-square, dengan menggunakan instrumen CES-D. Hasil: Hasil penelitian menemukan tidak ada hubungan antara jenis kelamin dan tingkat depresi pada mahasiswa semester VI, dengan nilai ρ=0,325 dari uji chi-square, yang menunjukkan tidak ada hubungan antara jenis kelamin dengan depresi. Kesimpulan: Dalam penelitian ini tidak ditemukan hubungan antara jenis kelamin dengan tingkat depresi pada mahasiswa.